Impacts of e-learning on high school students: The role of conventional interaction - Amarin Tawata (2018)
© Common Ground, Amarin Tawata, Pitipong Yodmongkol, Nopasit Chakpitak, and Pradon Sureephong. E-learning refers to technology used for learning, and it concerns interactions. No empirical study has explored e-learning interactions in conventional settings. This paper aims to examine how e-learning affects students' interactions during their technology use and in conventional settings. High school students, who were familiar with digital technologies in leisure time, and teachers were participants. The study designed short film production as an elearning activity, followed by interaction. It investigated how the activity affected the students' interactions, by means of triangulated interviews with participating teachers and students to explore the students' learning. The results showed that the short film productions led to frequent student-student and student-teacher interactions in online settings, for both academic and motivational purposes, because online technologies support easy interaction with other students and teachers, anywhere and anytime. Students saw that face-to-face interaction was more effective for motivational purposes. Students also interacted offline with parents and other school staff, including people in the community, to fulfill their learning. This implied that the students did not stop learning when they were not using digital technologies. For student- content interaction, the students preferred to use technology for learning and creating short films because it was easily accessible.